Cenozoic Evolution of the Sulu Sea Arc‐Basin System: An Overview. Issue 2 (17th February 2021) - Lai, Chun‐Kit; Xia, Xiao‐Ping; Hall, Robert; Meffre, Sebastien; Tsikouras, Basilios; Rosana Balangue‐Tarriela, Maria Ines; Idrus, Arifudin; Ifandi, Elena; Norazme, Nur 'aqidah
Abstract: The Cenozoic Sulu Sea arc‐basin system is situated in the tectonic junction between the South China Sea (SCS), northern Borneo, Palawan Continental Terrane, Philippine Mobile Belt, and Celebes Sea. We compare new/published geochronological and geochemical data from across the circum‐Sulu Sea region, and summarize seven major magmatic phases from the Middle Eocene to Pleistocene. The Middle Eocene (42.65 Ma) Sabah ophiolite and Eocene‐Oligocene (34‐33 Ma) Central Palawan ophiolite have MORB‐IAT‐transitional features, representing an intraoceanic subduction setting in the Paleogene northern Borneo and central‐southern Palawan. After the SCS opening (∼32 Ma) and ridge jump (∼25 Ma), late‐stage Proto‐SCS subduction (24‐21 Ma) may have formed the Panay arc andesite and the BABB magmatism in SW Zamboanga peninsula. Starting of final convergence between the Palawan Continental Terrane and northern Borneo‐SW Philippines (∼21 Ma) likely caused regional uplift/thrusting, forming the Top Crocker Unconformity and triggering the NW‐dipping Celebes Sea subduction. The subduction may have formed arc magmatism (21‐18 Ma) in the Cagayan ridge and its continuation in Panay and NE Sabah, and opened the NW Sulu Sea back‐arc basin through continental crust attenuation. Subduction rollback likely occurred in 17‐14 Ma and 13‐9 Ma, shifting arc magmatism southeast to the Sulu ridge and opening the SE Sulu Sea back‐arc basin. NW‐dipping Celebes Sea subduction largely ceased after ∼9 Ma, followed by extension‐related uplift/exhumation and 4‐0.2 Ma intraplate volcanism in northern Borneo. SE‐dipping Sulu Sea subduction likely occurred along the Negros‐Sulu trenches, and produced arc volcanism from ∼4 Ma. Plain Language Summary: The Sulu Sea and the adjacent sea basins (e.g., Celebes and SCS) are situated at the junction between the Eurasian, Philippine Sea, and Indo‐Australian plates. The opening and closure (when Australia‐Eurasia eventually collide) of these basins represent the final tectonic episode of the Neo‐Tethys, an ocean that separates the northern and southern continents. When and how these sea basins were created are long disputed. Here we present a regional tectonic reconstruction model by compiling new/published radiometric age and chemical data of major igneous suites from across the circum‐Sulu Sea region. Our model suggests that the Sulu Sea was formed by the NW‐dipping Celebes Sea subduction at ∼21 Ma, in response to the collision between the South China‐derived Palawan Continental Terrane and northern Borneo‐SW Philippines. The Sulu Sea basin may have continued to expand till ∼9 Ma, when NW‐dipping subduction of the Celebes Sea stopped. Afterward, to the west of the Sulu Sea, within‐plate extension in northern Borneo occurred and continues to the present‐day; whereas to the east, subduction of the Sulu Sea may have occurred along the Negros‐Sulu trenches, and produced arc volcanism from ∼4 Ma. Key Points: Age and geochemical data compilation for the circum‐Sulu Sea region summarized 7 Cenozoic (Mid Eocene to Pleistocene) magmatic phases After Palawan Continental Terrane accretion, Sulu Sea back‐arc basin was opened by Celebes Sea subduction (∼21 Ma) and rollback (17‐9 Ma) Northern Borneo underwent intraplate extension and magmatism after ∼9 Ma, and the Sulu Sea subducted along Sulu‐Negros trench from ∼4 Ma